Cannabinoid and cannabinoid related receptors in fibroblasts, inflammatory and endothelial cells of the equine hoof with and without laminitis: novel pharmacological target - Zamith Cunha, Rodrigo; Gobbo, Francesca; Morini, Maria; Salamanca, Giulia; Zanoni, Augusta; Bernardini, Chiara; Gramenzi, Alessandro; Chiocchetti, Roberto (Frontiers in Veterinary Science, 2025)
BackgroundEvidence suggests that the endocannabinoid system (ECS) is crucial for regulating inflammation, cell proliferation and pain. The ECS is composed of cannabinoid receptors such as type 1 (CBR1), type 2 (CBR2) and GPR55, endocannabinoids and enzymes. Proteins of ECS have previously been localized in the epidermal cells of the horse hooves. Given the physio-pathological role and cellular distribution of the ECS across species, the authors hypothesized that cannabinoid receptors are expressed within the inflammatory cells, fibroblasts and endothelial cells of the equine hoof laminae, going beyond the epidermal cells.ObjectivesTo preliminary analyze the gene expression of Cn1r, Cn2r and GPR55 in the hoof laminae and test the specificity of the antibody against GPR55. To characterize the distribution and expression of CBRs in the inflammatory cells and fibroblasts of the laminar junction of equine healthy hooves and with laminitis.AnimalsAnimals were divided into 3 groups: healthy, acute laminitis and chronic laminitis. A total of 18 samples were collected and processed from the front limb of animals slaughtered for consumption or euthanized (6 control animals, 4 acute laminitis, 8 chronic laminitis).MethodsAnalysis of CBR1, CBR2 and GPR55 protein expression was made by fluorescence microscopy with co-localization with antibodies against the macrophages marker IBA1, the T cell marker CD3, the neutrophils marker calprotectin (MAC387), the fibroblasts marker vimentin (Clove V9) and the nerve fibers marker Substance P. Preliminary analysis was performed to evaluate gene expression (Cnr1, Cnr2, and Gpr55) using real-time PCR and to verify the specificity of the primary antibody (Gpr55) with Western Blotting (WB).ResultsThe resident pool of inflammatory cells in the normal laminae and the inflammatory infiltrate cells of the affected equine laminae showed protein expression of CB2R and GPR55; no CB1R staining was seen at the inflammatory cells. Equine dermal fibroblast and endothelial cells exhibited protein expressions of CB1R, CBR2 and GPR55. Substance P positive nerve fibers were positive for CB1R.Conclusions and clinical importanceCannabinoid receptors are expressed in different immune cell types of the hoof laminae, pointing to the role of the ECS in modulating inflammatory outburst, tissue degeneration and pain. Our results serve as a foundation for the development of new veterinary pharmacotherapies that target the ECS during laminitis.